Fictions of the Territory: Writing and Landscape(s) in Tratado de arqueología peruana by Roberto Zariquiey - Hernández, Biviana (2021)
In this article we will address the interdisciplinary condition of Roberto Zariquiey’s Tratado de arqueología peruana from the notion of territory as a referential space of Peruvian geography and culture. To this end, we will focus on some of the landscapes that characterize the three geographical areas in which the national territory of Peru is divided —the Costa, the Sierra, the Selva—, and which are key to understanding the two dimensions in which the textuality of Zariquiey’s poetry-treatise: as a rewriting of the subjective meanings of the communities of the past and as an appropriation of the code / language of the social sciences to produce a text that oscillates between poetry and archeology.